Influence of water volumes stored in the Sibinacocha lake in the 2nd rehabilitation stage of Macchupicchu Hydropower Plant - Sarango, Douglas (2018)
This research was made in the hydraulic system of the Hydropower Plant Machupicchu, which has water reserves stored in Sibinacocha lake with a maximum capacity up to 100 million cubic meters. The power plant Mahupicchu was buried in February 1998 by slipping the Ahobamba streams, initiates a first stage of recovery in 2001 achieving sustained generate up to 90 MW and guaranteed by the reserves of the Sibinacocha lake. In the second stage of rehabilitation, initiated in 2009, it aims to increase the generation of 90 MW to 180 MW requiring 61 m3 /s in times of ood and drought, which means requirements higher water volumes stored in Sibinacocha lake. The research simulates the operation of the lake for 47 years (1965 to 2011) considering the requirement of the first and second stage of rehabilitation. The simulation was done with the model Reservoir System Analysis (HEC-3). The simulation results of the rst. rehabilitation stage indicate that the design flow of 30 m3 /s is supplied by 100 % over the simulation period. While the simulation results for the second rehabilitation stage, indicate that the total ow design of the plant of 61 m 3 /s will only be supplied in times of avenues by 100 %, while in the dry season can not supply this flow